Assessing predictors of self-management intentions in people with type 2 diabetes - Yogarabindranath Swarna Nantha; Tan Yan Shan; Shamsul Haque; Anuar Zaini Md Zain (BMC, 2022)
Abstract Background Type 2 diabetes mellitus (T2D) is slowly turning into an international health emergency, evidenced by accelerated growth in prevalence rates worldwide. Experts have now called for greater integration of self-management interventions in clinical practice in light of these worrisome trends, supplanting the prevailing notion of a "glucocentric" approach. In this pilot study designed to complement a novel assessment program currently in development, we describe a concise screening tool designed to stratify the intention to follow through on self-management practices in people with T2D. Methods A cross-sectional survey was conducted at 3 regional primary care clinics. Individuals with T2D having the following characteristics were recruited into the study: (i) individuals with T2D between 18 and 65 years, (ii) fluent in English and, and iii) having been diagnosed with T2D for at least 2 years. We assessed the relevance of components in the Theory of Planned Behaviour (TPB) within the context of self-management behaviour in T2D. Participants were requested to complete a questionnaire containing questions related to intention, attitudes subjective norm and perceived behavioural control. Based on their responses, the psychometric properties of the scale were then evaluated using both reliability and validity analysis. Results The Cronbach α value for all direct measures of TPB was excellent: intention to adhere to self-management practices (0.98), attitude towards self-management behaviour (0.87), subjective norm (0.83), and perceived behaviour control (0.66). The correlation between intentions and all 3 constructs of TPB was excellent (p < 0.01). Structural equation modeling helped determine attitudes and subjective norms as important predictors of intentions to follow through self-management practices. Conclusions By first understanding the dimensions that influence intentions associated with self-management behaviour, clinicians have the opportunity to "triage" individuals with T2D who require greater involvement to bring about better self-care practices. Thus, our research attempts to bridge this gap by devising a psychometric tool suited to a regional setting which allows for an improved person-centered communication between clinicians and patients.